Antibiotic prescribing for adults with acute cough/lower respiratory tract infection: congruence with guidelines. - Wood, J; Butler, C; Hood, K; Kelly, M; Verheij, T; Little, P; Torres, A; Blasi, F; Schaberg, T; Goossens, H; Nuttall, J; Coenen, S (2011)
European guidelines for treating acute cough/lower respiratory tract infection (LRTI) aim to reduce nonevidence-based variation in prescribing, and better target and increase the use of first-line antibiotics. However, their application in primary care is unknown. We explored congruence of both antibiotic prescribing and antibiotic choice with European Respiratory Society (ERS)/European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guidelines for managing LRTI. The present study was an analysis of prospective observational data from patients presenting to primary care with acute cough/LRTI. Clinicians recorded symptoms on presentation, and their examination and management. Patients were followed up with self-complete diaries. 1,776 (52.7%) patients were prescribed antibiotics. Given patients' clinical presentation, clinicians could have justified an antibiotic prescription for 1,915 (71.2%) patients according to the ERS/ESCMID guidelines. 761 (42.8%) of those who were prescribed antibiotics received a first-choice antibiotic (i.e. tetracycline or amoxicillin). Ciprofloxacin was prescribed for 37 (2.1%) and cephalosporins for 117 (6.6%). A lack of specificity in definitions in the ERS/ESCMID guidelines could have enabled clinicians to justify a higher rate of antibiotic prescription. More studies are needed to produce specific clinical definitions and indications for treatment. First-choice antibiotics were prescribed to the minority of patients who received an antibiotic prescription.